Respuesta :
f(x) = 8x - 13
g(x) = x - 9
(f + g)(x) = f(x) + g(x)
f(5) = 8 · 5 - 13 = 40 - 13 = 27
g(5) = 5 - 9 = -4
(f + g)(5) = f(5) + g(5) = 27 + (-4) = 23
Answer: A.) 23
g(x) = x - 9
(f + g)(x) = f(x) + g(x)
f(5) = 8 · 5 - 13 = 40 - 13 = 27
g(5) = 5 - 9 = -4
(f + g)(5) = f(5) + g(5) = 27 + (-4) = 23
Answer: A.) 23
Answer:
Option A is correct
[tex](f+g)(5)[/tex] = 23
Step-by-step explanation:
Given the functions:
f(x) = 8x-13
g(x) = x-9
Solve: [tex](f+g)(5)[/tex]
First calculate:
[tex](f+g)(x) = f(x)+g(x)[/tex]
Substitute the given values we have;
[tex](f+g)(x) = 8x-13+x-9 = 9x-22[/tex]
Put x = 5 above we have;
[tex](f+g)(5) = 9(5)-22 = 45-22=23[/tex]
Therefore, the value of [tex](f+g)(5)[/tex] is 23